A Beginner's Guide to Water Management—Water Clarity - Florida LAKEWATCH; Mark Hoyer (EDIS, 2001)
Water clarity is one of the most noticeable attributes of a waterbody. It's also of great importance to many people. However, crystal clear water is not the ruler by which all lakes should be measured. As you'll learn in this circular, lakes with a wide range of water clarity occur naturally in Florida. Anyone interested in the subject can benefit from reading this basic introduction. Topics range from how we measure water clarity, what affects it, the relationship between water clarity and biological productivity, and techniques used for managing water clarity in lakes. Mathematical models are introduced as a way of predicting water clarity in lakes. This reader-friendly booklet is 33 pages in length and includes numerous photographs and figures. First published Sept. 2001.